2018
DOI: 10.1002/aoc.4361
|View full text |Cite
|
Sign up to set email alerts
|

New dimeric Schiff base quinoline complexes: Synthesis, spectral characterization, electrochemistry and cytotoxicity

Abstract: A novel Schiff base ligand (H-DPPMHQ) derived from 2-hydrazineylquinoline and 1,3-diphenyl-1H-pyrazole-5-carbaldehyde and its dimeric complexes with compositions [Cr(DPPMHQ)Cl] 2 ⋅2Cl and [M(DPPMHQ)Cl] 2 (where M = Cu(II), Co(II), Ni(II) and Zn(II)) have been synthesized and characterized using physicochemical methods like elemental analysis, magnetic susceptibility and molar conductivity measurements, multispectral techniques and electrochemical studies. The molar conductance data reveal that all metal chelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…The molecular ion peak for 12 is observed at m / z 868.25. Other peaks due to (M + H + Br 79 ) and (M + H + Br 81 ) isotopes were observed at 870.30, 872.30 which confirms the stoichiometry of the complexes . Thus, the mass spectral results along with elemental analyses agreed with formation of [M(L 2 ) 2 ⋅2H 2 O] type complexes in 1:2 molar stoichiometry.…”
Section: Resultssupporting
confidence: 68%
“…The molecular ion peak for 12 is observed at m / z 868.25. Other peaks due to (M + H + Br 79 ) and (M + H + Br 81 ) isotopes were observed at 870.30, 872.30 which confirms the stoichiometry of the complexes . Thus, the mass spectral results along with elemental analyses agreed with formation of [M(L 2 ) 2 ⋅2H 2 O] type complexes in 1:2 molar stoichiometry.…”
Section: Resultssupporting
confidence: 68%
“…In the electronic spectra of Cu (II) complexes, UV spectral bands were observed in vicinity of 15,275–15530 cm −1 and 24,300–24,850 cm −1 which were attributed for 2 B 1 g → 2 A 1 g (ν 1 ) 2 B 1 g → 2 E 2 g (ν 2 ) transitions, respectively and the magnetic moment values lies in the range of 1.82–1.92 BM corresponds to octahedral geometry …”
Section: Resultsmentioning
confidence: 96%
“…Particle size for the hybrids was calculated using maximum intensity peak by the standard Scherrer equation : normalD=/()βcosθ where D is the particle size; K is a constant (= 0.97); k is X‐ray wavelength ( λ = 1.5568 Ǻ); θ is Bragg diffraction angle and β is integral peak width which is converted into radian while calculation. On the other hands, the values obtained for all the complexes were in the range 46–73 nm which indicated that the particles were of nano‐size . On the other hand, the values of size of particles of Cu (II), Co (II) and Zn (II) complexes were observed at 63.84, 48.47 and 52.63 nm, respectively and these values calculated by using the highest intensity value.…”
Section: Resultsmentioning
confidence: 89%